2021
DOI: 10.1097/md.0000000000026779
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant PTEN, PIK3CA, pMAPK, and TP53 expression in human scalp and face angiosarcoma

Abstract: Angiosarcoma is a rare, highly aggressive malignant tumor originating from endothelial cells that line the lumen of blood or lymphatic vessels. The molecular mechanisms of scalp and face angiosarcoma still need to be elucidated. This study aimed to investigate the expression of phosphatase and tensin homolog (PTEN), phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), phosphorylated mitogen-activated kinase-like protein (pMAPK), and tumor protein p53 (TP53) in scalp and face angiosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Corradini et al 114 identified PTEN mutants in 50% in radiotherapy-induced ASs. 114 Studies showed that AS has weak PTEN immunoreactivity, 115 and in high-grade tumours PTEN expression was largely absent. 116 Human and canine tumours share PTEN mutants not only in the case of AS, 115,[117][118][119] but also in mammary tumours and gliomas.…”
Section: Alterations Of Intracellular Signalling Pathways and Importa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Corradini et al 114 identified PTEN mutants in 50% in radiotherapy-induced ASs. 114 Studies showed that AS has weak PTEN immunoreactivity, 115 and in high-grade tumours PTEN expression was largely absent. 116 Human and canine tumours share PTEN mutants not only in the case of AS, 115,[117][118][119] but also in mammary tumours and gliomas.…”
Section: Alterations Of Intracellular Signalling Pathways and Importa...mentioning
confidence: 99%
“…114 Studies showed that AS has weak PTEN immunoreactivity, 115 and in high-grade tumours PTEN expression was largely absent. 116 Human and canine tumours share PTEN mutants not only in the case of AS, 115,[117][118][119] but also in mammary tumours and gliomas. 27 Inactivating PTEN mutation in HSA was detected in between 6% and 15% of cases 13 in several independent studies based on exome sequence analyses, mostly together with TP53 mutation.…”
Section: Alterations Of Intracellular Signalling Pathways and Importa...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the quality miRNAseq control, all samples exhibited a phred value ranging from 35 to 40. Phred levels are typically categorised as poor (0-20), medium (20)(21)(22)(23)(24)(25)(26)(27)(28), and good (>28). Therefore, all samples demonstrated high quality.…”
Section: The Subsequent Qpcr Experiments Validated the Consistency Ofmentioning
confidence: 99%
“…10 Recent research has demonstrated that the PTEN pathway is frequently disrupted in canine haemangiosarcoma, either through inactivating mutations or epigenetic downregulation. 3,[11][12][13] MicroRNAs (miRNAs) are small RNA molecules, typically [18][19][20][21][22][23][24][25] nucleotides in length, that are highly conserved and noncoding. They play a crucial role in gene expression regulation following transcription by specifically binding to complementary target messenger RNAs (mRNAs).…”
Section: Introductionmentioning
confidence: 99%